An Empirical Investigation of the Effect of Interaction Justice Perception on Consumer Intentions After Complaining - Bhandari , Mahesh S.; Polonsky , Michael J. (Journal of Law and Governance, 2007)
This study examined how apology as interaction justice impacts on consumer perceptions of service recovery attempt. Data was collected using hypothetical scenarios. Two types of service failures were proposed and the impact of recovery action on each failure type was compared. Findings include that there is direct effect of recovery action on consumer future intentions in both type of failures. Implications and direction to the future research were proposed.